Design and Implementation of a Smart Traffic Control Signal for Suburban Areas: A Case Study of Tarkwa-Nsuaem - Ampem, Isaac Aboagye; Arkorful, Isaac Papa Kwesi; Dwomoh, Lambert; Sefa-Boateng, Yaw (MSD Institute, 2025)
With the increasing number of cars in suburban areas like Tarkwa-Nsuaem, expensive approaches to expanding road infrastructure are financially impractical for a lower-middle-income country like Ghana. Traffic accidents, causing 1.25 million deaths, up to 50 million injuries annually, and a global ratio of 18 deaths per 100,000 people, demand cost-effective prevention solutions for these suburban communities. This study proposes an ultrasonic sensor-based traffic control system using an HC-SRO4 ultrasonic sensor and an Arduino Nano with an ATMEGA 328P microcontroller. Simulated using Proteus 8 Professional and Arduino 1.6.7 software, the system optimizes traffic flow by eliminating the standard 60-second red light wait time. Vehicles on byways move freely unless a vehicle is sensed on the connecting highway, in which case the wait time is reduced to under 30 seconds. This low-cost, adaptive approach enhances road safety and efficiency, making it a viable alternative for traffic management in resource-constrained suburban communities.